Perioperative Management of an Adult Patient With Myoclonic Epilepsy With Ragged Red Fibers Syndrome: A Case Report. Issue 2 (11th February 2021) - Valent, Arnaud; Pharaboz, Alexandre; Letord, Alexia; Boughezala, Samia; Boccara, David; Plaud, Benoit
Abstract : Myoclonic epilepsy with ragged red fibers (MERRF) syndrome is a rare mitochondrial disease potentially associated with increased sensitivity to anesthesia and metabolic decompensation. We present the perioperative management in a 59-year-old man with MERRF scheduled for lipomatosis cure under general anesthesia (GA). Following a reduced fasting period, the patient had an uneventful balanced GA with propofol, sevoflurane, and rocuronium. The patient did not present metabolic decompensation nor malignant hyperthermia but prolonged neuromuscular blockade. Propofol and sevoflurane may be used in asymptomatic MERRF adult patients. Such patients present high risk of residual neuromuscular blockade that should be monitored and reversed.